2018
DOI: 10.1007/s40430-018-1008-9
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of plastic strain and microstructure on elastic modulus reduction in advanced high-strength steels

Abstract: Increase in the use of the advanced high-strength steels (AHSS) is an interesting alternative to automotive industry to reduce vehicle weight and fuel consumption. However, it has been limited due to challenges in formability, tool life, and springback. The springback is pointed in the literature as one of the challenges that involves the mass production of structural components and the aspects that shows influence are still not fully understood. There is still a gap in the literature to analyze the elastic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Fundamental mechanical properties and true stress vs true strain curve obtained by [15]. Errors obtained by computational models for a BHL of (a), 80tf (b) and 130tf (c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fundamental mechanical properties and true stress vs true strain curve obtained by [15]. Errors obtained by computational models for a BHL of (a), 80tf (b) and 130tf (c).…”
Section: Discussionmentioning
confidence: 99%
“…These values were used to implement the FLC criteria in the computational model. The fundamental mechanical properties and true stress-by-true strain curve for DP600 steel obtained by [15] as illustrated in Fig. 5 were also used.…”
Section: Methodsmentioning
confidence: 99%
“…is the rate of decrease with the increase of the plastic strain, p  [8]. Figure 2 presents a comparison between the numerical model reported for the two materials (labelled EMD) by the benchmark committee [4] and values reported in other studies for steels [7,9]. The analysis shows that the model suggested and adopted in this study leads to a trend like the one reported in other studies, although the variation is slightly higher for the DP980 steel under analysis than the one considered in [9].~ Both materials show a negligeable variation of the in-plane distribution of the flow stress.…”
Section: Elastic Propertiesmentioning
confidence: 99%
“…Barsanti et al [17] demonstrated that considering the elastic modulus degradation of steel due to plastic strain could enhance the precision of fatigue analysis. Lajarin et al [18] showed that the degradation of elastic modulus was dependent on both the plastic strain and the anisotropy of the material. The elastic modulus decrease of TRIP780 steel in 0, 45 and 90 to rolling direction could reach 28.5%,24.2% and 20.4%, respectively.…”
Section: Introductionmentioning
confidence: 99%